THE EFFECT OF THE IMPLEMENTATION OF TAX PLANNING ON INCOME TAX PAYMENTS (STUDY ON THE CONSUMER GOODS INDUSTRY SECTOR IDX 2021 PERIOD) - ALLFRIENDO FRIDES OXITO SAGALA; HEROLD MOODY MANALU (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
Taxes are one of the sources of state revenue which will then be managed by the state to engineer economic activities, including financing the state budget to support the welfare of the community. Therefore, the management of government spending depends on tax revenues. One of the sources of state revenue is through corporate income tax. Therefore, this study aims to determine the application of tax planning to the payment of corporate income tax. The data used are quantitative data processed based on the causal associative descriptive method. Obtained 44 samples from 53 companies listed on the IDX. The results showed that tax planning has a very low relationship with the direction of positive relationships. The significance test resulted in that tax planning had an insignificant influence on corporate income tax revenues for the government with a contribution of 0.8%.